SUKU ANAK DALAM DICTIONARY: DOCUMENTING CULTURAL ITEMS OF ENDANGERED INDIGENOUS LANGUAGE - Putri Ayu Lestari; Zainuddin .; I Wayan Dirgeyasa (Universitas Negeri Medan, 2020)
A number of ecological linguists, using critical discourse analysis, have found that between culture, language, and biodiversity has a correlation. One of them is Suku Anak Dalam or called Orang Rimba. Suku Anak Dalam is a semi nomadic ethnic group living in National Park of Bukit Dua Belas, Jambi Province. The language is indigenous and endangered so that it must be documented. The speakers of a language will lose their language; even language is often regarded as a symbol of tribal identity or national identity. In the midst of the widespread use and dissemination of foreign vocabulary, some regions still maintain the cultural vocabulary that characterizes the region. This research was conducted for the reason of collecting the lexical items from Suku Anak Dalam language into a dictionary. This research and development aimed to find out and examine the cultural items needed by dictionary of Suku Anak Dalam language. Keywords: Suku Anak Dalam Language, Designing, Software Dictionary, Indegeneous language